Block-copolymer-like self-assembly behavior of mobile-ligand grafted ultra-small nanoparticles. Issue 24 (26th May 2021) - Xu, Feng-Rui; Shi, Rui; Jia, Xiang-Meng; Chai, Sheng-Chao; Li, Hao-Long; Qian, Hu-Jun; Lu, Zhong-Yuan
Abstract : We use coarse-grained molecular dynamics simulations to study the self-assembly behavior of polyoxometalate (POM) nanoparticles (NPs) decorated with mobile polymer ligands under melt conditions. Abstract : We use coarse-grained molecular dynamics simulations to study the self-assembly behavior of polyoxometalate (POM) nanoparticles (NPs) decorated with mobile polymer ligands under melt conditions. We demonstrate that due to the mobile nature of the grafted ligands on the NP surface, NPs have the ability to expose a part of their surfaces, leading to a block-copolymer-like self-assembly behavior. The exposed NP surface serves as one block and the grafted ligand polymers as another. This system has a strong ability to self-assemble into long-range ordered structures such as block copolymers due to large incompatibility between POM and ligand polymers, i.e., POM NPs can form lamellar, cylindrical, and spherical structures, which are consistent with previous experimental results. More importantly, these ordered structures are on the sub-10 nm scale, which is an important requirement for many applications. At low graft density, we find a new inverse-cylindrical structure formation where polymers form cylinders and POMs form a continuous network structure. A full self-assembly phase diagram is constructed which illustrates rules to manipulate the self-assembly structures of NPs decorated with mobile polymer ligands. We hope that these computational results will be useful for the new design of nanostructures with improved optical or electronic functions.